Proximal tibia fracture dislocations: Management and outcomes of a severe and under-recognized injury. Issue 3 (March 2022) - Keil, Lukas G.; Mullis, Brian H.; III, Paul Tornetta; Alley, Maxwell C.; Olszewski, Nathan P.; Wheeler, Jonathan A.; von Kaeppler, Ericka P.; Morshed, Saam; Matar, Robert N.; Archdeacon, Michael T.; Smith, Tyler W.; Miller, Anna N.; et al.
Highlights: Proximal tibia fracture dislocations (PTFDs) represent 4% of proximal tibia fractures. PTFDs are often unicondylar and may go unrecognized. Malunion is common, and PTFD outcomes may be worse than bicondylar fractures. Abstract: Introduction: Proximal tibia fracture dislocations (PTFDs) are a subset of plateau fractures with little in the literature since description by Hohl (1967) and classification by Moore (1981). We sought to evaluate reliability in diagnosis of fracture-dislocations by traumatologists and to compare their outcomes with bicondylar tibial plateau fractures (BTPFs). Methods: This was a retrospective cohort study at 14 level 1 trauma centers throughout North America. In all, 4771 proximal tibia fractures were reviewed by all sites and 278 possible PTFDs were identified using the Moore classification. These were reviewed by an adjudication board of three traumatologists to obtain consensus. Outcomes included inter-rater reliability of PTFD diagnosis, wound complications, malunion, range of motion (ROM), and knee pain limiting function. These were compared to BTPF data from a previous study. Results: Of 278 submitted cases, 187 were deemed PTFDs representing 4% of all proximal tibia fractures reviewed and 67% of those submitted. Inter-rater agreement by the adjudication board was good (83%). Sixty-one PTFDs (33%) were unicondylar. Eleven (6%) had ligamentous repair and 72 (39%) had meniscal repair. Two required vascular repair. Infection was more common among PTFDs than BTPFs (14% vs 9%, p = 0.038). Malunion occurred in 25% of PTFDs. ROM was worse among PTFDs, although likely not clinically significant. Knee pain limited function at final follow-up in 24% of both cohorts. Conclusions: PTFDs represent 4% of proximal tibia fractures. They are often unicondylar and may go unrecognized. Malunion is common, and PTFD outcomes may be worse than bicondylar fractures.